GENEALOGY OF INTERPRETATION OF THE VARSE ON WOMENS PUBLIC SPACE: COMPARATIF STUDY OF KITAB AT-TABARI, AL_MAWARDI AND SAYYID QUTB: Genealogi Tafsir Ayat Ruang Publik Perempuan: Studi Komparatif Kitab Tafsir al-Tabari, al-Mawardi, dan Sayyid Qutb - Taufiqur Rahman; Nabelatus Sholihah; Muzayyin; Nurul Qamariyah (Mozaic: Islamic Studies Journal, 2024)
This research examines the genealogy of Qur'anic exegesis on verses concerning women's public space through a comparative study of three representative works from different periods: Jāmi‘ al-Bayān by al-Ṭabarī (classical), al-Nukat wa al-‘Uyūn by al-Māwardī (medieval), and Fī Ẓilāl al-Qur’ān by Sayyid Quṭb (contemporary). Employing a qualitative approach with Michel Foucault's genealogical analysis and Amina Wadud's feminist hermeneutics, the study aims to uncover the discursive formations that shaped these interpretations and their relevance to social justice. The findings reveal that al-Ṭabarī represents a narration-based reasoning that is relatively neutral yet inherits misogynistic traditions; al-Māwardī develops normative juridical reasoning that systematically restricts women's public access; while Sayyid Quṭb offers a moderate ideological reading that nevertheless maintains domestic priorities. The dominant discursive formations in each era narration, jurisprudence, and ideological movement prove to be the primary determinants shaping exegesis. The continuity of patriarchal assumptions across periods demonstrates that resistance to women's public participation stems from social constructions and power relations, not merely from the Qur'anic text itself. This research contributes to the development of gender-just exegetical epistemology in Indonesia.